1999
DOI: 10.1029/1999jd900010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of ENSO to snowfall and related cyclone activity in the contiguous United States

Abstract: Mexico was above normal during E1 Nifio events and below normal during La Nifia events. In this paper, we examine the relationship of ENSO to snowfall for the entire United States, expanding on these earlier regional studies. Data and Methods of Analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 14 publications
4
69
0
Order By: Relevance
“…There were more southwesterly and deepening low events during EN years (38% and 10%, respectively) than in NEU years (24% and 5%, respectively), which would be consistent with the predominance of the negative PNA pattern [troughing (ridging) over the western (eastern) US -see Keables et al 1992 andChern (1995)] over the US during these years. More NEU year events which produce heavier snow fall events during the NPO1 time period is also consistent with the results of Kunkel and Angel (1999). Also, fewer, but deeper, EN snowfall producing events found here are consistent with those of Martins and Smith (2003), and the time period they study mostly contains the NPO1 period.…”
Section: B Long Term Trendssupporting
confidence: 82%
See 4 more Smart Citations
“…There were more southwesterly and deepening low events during EN years (38% and 10%, respectively) than in NEU years (24% and 5%, respectively), which would be consistent with the predominance of the negative PNA pattern [troughing (ridging) over the western (eastern) US -see Keables et al 1992 andChern (1995)] over the US during these years. More NEU year events which produce heavier snow fall events during the NPO1 time period is also consistent with the results of Kunkel and Angel (1999). Also, fewer, but deeper, EN snowfall producing events found here are consistent with those of Martins and Smith (2003), and the time period they study mostly contains the NPO1 period.…”
Section: B Long Term Trendssupporting
confidence: 82%
“…There was little trend in the total number of snowfall events in spite of a general increase in precipitation (Hu et al, 1998;Karl and Knight, 1998) Midwest region as well. Kunkel and Angel (1999) found that strong LN years produced more snowfall over the mid-Missouri region. Thus, examining the type of snowfall events that occur in this region may bridge the gap between the results of this study and the published results described above.…”
Section: B Long Term Trendsmentioning
confidence: 99%
See 3 more Smart Citations